Effect of feeding a low-vitamin A diet on carcass and production characteristics of steers with a high or low propensity for marbling. (10th November 2020) - Knutson, E. E.; Menezes, A. C. B.; Sun, X.; Fontoura, A. B. P.; Liu, J. H.; Bauer, M. L.; Maddock-Carlin, K. R.; Swanson, K. C.; Ward, A. K.
Abstract : Our research group demonstrated that vitamin A restriction affected meat quality of Angus cross and Simmental steers. Therefore, the aim of this study is to highlight the genotype variations in response to dietary vitamin A levels. Commercial Angus and Simmental steers ( n = 32 per breed; initial BW = 337.2 ± 5.9 kg; ~8 months of age) were fed a low-vitamin A (LVA ) (1017 IU/kg DM) backgrounding diet for 95 days to reduce hepatic vitamin A stores. During finishing, steers were randomly assigned to treatments in a 2 × 2 factorial arrangement of genotype × dietary vitamin A concentration. The LVA treatment was a finishing diet with no supplemental vitamin A (723 IU vitamin A/kg DM); the control (CON ) was the LVA diet plus supplementation with 2200 IU vitamin A/kg DM. Blood samples were collected at three time points throughout the study to analyze serum retinol concentration. At the completion of finishing, steers were slaughtered at a commercial abattoir. Meat characteristics assessed were intramuscular fat concentration, color, Warner-Bratzler shear force, cook loss and pH. Camera image analysis was used for determination of marbling, 12th rib back fat and longissimus muscle area (LMA ). The LVA steers had lower ( P < 0.001) serum retinol concentration than CON steers. The LVA treatment resulted in greater ( P = 0.03) average daily gain than the CON treatment, 1.52 and 1.44 ± 0.03 kg/day, respectively; however, there was no effect of treatment on final BW, DM intake or feed efficiency. Cooking loss and yield grade were greater and LMA was smaller in LVA steers ( P < 0.05). There was an interaction between breed and treatment for marbling score ( P = 0.01) and percentage of carcasses grading United States Department of Agriculture (USDA ) Prime ( P = 0.02). For Angus steers, LVA treatment resulted in a 16% greater marbling score than CON (683 and 570 ± 40, respectively) and 27% of LVA Angus steers graded USDA Prime compared with 0% for CON. Conversely, there was no difference in marbling score or USDA Quality Grades between LVA and CON for Simmental steers. In conclusion, feeding a LVA diet during finishing increased marbling in Angus but not in Simmental steers. Reducing the vitamin A level of finishing diets fed to cattle with a high propensity to marble, such as Angus, has the potential to increase economically important traits such as marbling and quality grade without negatively impacting gain : feed or yield grade.